2020
DOI: 10.1186/s12970-020-0335-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbohydrate supplementation on aerobic exercise performance during acute high altitude exposure and after 22 days of acclimatization and energy deficit

Abstract: Background: The ergogenic effects of supplemental carbohydrate on aerobic exercise performance at high altitude (HA) may be modulated by acclimatization status. Longitudinal evaluation of potential performance benefits of carbohydrate supplementation in the same volunteers before and after acclimatization to HA have not been reported. Purpose: This study examined how consuming carbohydrate affected 2-mile time trial performance in lowlanders at HA (4300 m) before and after acclimatization. Methods: Fourteen un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
(38 reference statements)
1
19
0
Order By: Relevance
“…Interestingly, carbohydrate supplementation had no effect on 3 km time trial performance. This is in agreement with Bradbury et al (17) who observed no difference in time trial performance…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Interestingly, carbohydrate supplementation had no effect on 3 km time trial performance. This is in agreement with Bradbury et al (17) who observed no difference in time trial performance…”
Section: Discussionsupporting
confidence: 93%
“…As such, it seems likely that muscle glycogen concentration did not reach a critical threshold (< 70 mmol•kg -1 wet weight) in which it may be expected calcium release from the sarcoplasmic reticulum is impaired, and subsequently peak power output reduced (41). This hypothesis may also explain the null findings observed by Bradbury et al (17), as they utilised similar experimental design. Despite the novel findings reported in this study, several limitations must be acknowledged.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the end of the stay, SpO 2 following exercise remained unchanged or increased by 3% [ 63 , 76 , 77 ]. In the studies lasting from seven to 22 days, SpO 2 declined by −15% to −23% during exercise tests at acute hypoxia [ 60 , 66 , 68 , 78 ]. In these studies, the rise in SpO 2 during acclimatization ranged from 2% to 10%.…”
Section: Part 2: Results From the Literature Reviewmentioning
confidence: 99%
“…Exercising HR at acute altitude exposure increased by 11 bpm to 38 bpm in six out of seven studies when compared to sea level. In the remaining two studies, reporting either 55% slower time trial durations [ 78 ] or significant reductions in mean power [ 77 ], exercising HR during acute altitude exposure declined in a range of −1 bpm to −7 bpm. In those studies, showing a primary increase in HR during the first exercise test, the reduction in exercising HR ranged from −4 bpm to −8 bpm [ 60 , 63 , 66 , 76 ], still being elevated compared to sea level.…”
Section: Part 2: Results From the Literature Reviewmentioning
confidence: 99%